라식 수술 전과 후의 사위도 비교 - 허성인; 전인철; 마기중 (대한시과학회지, 17(1), 2015)
목 적: 라식 수술 전과 후의 사위도를 비교하여 차이가 있는지 알아보고자 하였다. 방 법: 전신질환이나 안질환이 없고 교정시력이 1.0 이상인 20~40세 사이의 40명(남자 17명, 여자 23명, 평균 연령 27.67±6.15세)을 대상으로 수술 전과 수술 후 1개월째 각각 자각식 굴절검사, 원거리 사위도, 근거리 사위도, PD 및 계산 AC/A 비를 측정하였다. 결 과: 수술 전과 후 등가구면굴절력은 -4.72±2.08D와 -0.03±0.16D로 -4.69±2.06D의 변화를 보였다. 수술 전과 후의 원거리 사위는 0.81±1.75Δ 외사위와 0.73±1.75Δ 외사위로 외사위도가 0.09±0.41Δ 감소하였으나 통계적으로 유의하지 않았다(p=0.181). 수술 전과 후의 근거리 사위는 2.91±3.91Δ 외사위에서 3.44±4.02Δ 외사위로 0.53±0.91Δ 유의한 증가를 보였다(p=0.001). 그러나 라식수술 전후 근거리 물체를 볼 때 원용안경이 폭주와 조절에 미치는 영향을 보정하였을 때 근거리 사위는 수술 전 4.57±3.94Δ 외사위였고, 수술 후 3.48±4.02Δ 외사위로, 1.09±1.19Δ 유의하게 감소하였다(p=0.000). 결 론: 수술 전과 후에 측정한 원거리 사위는 유의한 변화가 없었다. 근거리 사위는 수술 후 외사위 방향으로 증가하였으며, 수술 전과 후 측정 조건이 다르기 때문에 원용안경의 기저내방효과와 조절 효과를 보정한 후 동일한 조건에서 비교했을 때에는 근거리사위도가 내사위 방향으로 증가하였다. 그러나 근거리사위도가 정상범위에 속하기 때문에 라식수술에 의한 사위도 변화가 안정피로를 유발하지는 않을 것으로 생각된다. Purpose: This study aims to investigate the changes of heterophoria before and after LASIK surgery. Methods: 40 subjects in their 20s and 30s participated in this study, who had neither a systemic disease nor an ocular disease and whose corrected visual acuity was 1.0 or better. We measured the refractive error, heterophoria, pupillary distance and calculated AC/A ratio before and one month after LASIK surgery. Result: Subjects’ spherical equivalent was -4.72±2.08D before the surgery and -4.69±2.06D after the surgery, and the difference was -0.03±0.16D. Out of the 40 subjects, 10 still had myope, 21 became emmetrope, and 9 experienced hyperope. In the distance phoria before and after LASIK surgery, the exophria was reduced from 0.81±1.75Δ to 0.73±1.75Δ, and the difference was 0.09±0.41Δ, but it was not statistically significant (p=0.181). In the near phoria before and after the surgery, the exophoria increased from 2.91±3.91Δ to 3.44±4.02Δ, and the difference was 0.53±0.91Δ, which was statistically significant (p=0.001). However, when the effectivity of a spectacle lens for distance was corrected for near target before and after LASIK surgery, the exophoria decreased from 4.57±3.94Δ to 3.48±4.02Δ, and the difference was 1.09±1.19Δ (p=0.001). Conclusion: When the distance phoria was measured before and after the surgery, there was no significant difference. The near phoria increased in the direction of the exophoria after the surgery, but since the measurement conditions before the surgery were different from those after the surgery, it is necessary to compare it in the same conditions after correcting the base-in effect and the accommodation effect of a spectacle lens for distance, and there was significant decrease to esophoria direction in the near phoria after the effect caused by a spectacle lenses for distance was corrected. But there was considered that the change of near phoria caused by LASIK surgery did not induced asthenopia because of near poria showed in normal range. KCI Citation Count: 2